2006
DOI: 10.1590/s0034-72992006000500012
|View full text |Cite
|
Sign up to set email alerts
|

Polimorfismos GSTT1 e GSTM1 em indivíduos tabagistas com carcinoma espinocelular de cabeça e pescoço

Abstract: Gene variability related to carcinogen activation and detoxification may interfere with susceptibility to head and neck cancer. Aim: To investigate the relation between GSTT1 and GSTM1 null polymorphisms and the risk of head and neck squamous cell carcinoma in cigarette smokers. Material and Method: A case-control study conducted at the Sao Jose do Rio Preto Medical School, Brazil. GSTM1 and GSTT1 null genotype frequencies were evaluated by multiplex PCR in 45 cigarette smokers with head and neck squamous cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
2
1
1
Order By: Relevance
“…[38][39][40][41] In a multivariate logistic analysis, we have evidenced that the GSTT1/GSTM1*0 ([ ]/ [-]) combined genotype provides a greater susceptibility for the development of spinocellular carcinoma of head and neck, similar results to those found by other authors. 7,23,42,43 Various studies could not correlate the null GSTT1 genotype with the head and neck cancer, 26,27,43 which was a result found in our study. Similarly, there was no association between this type of neoplasia and the null combined genotypes null GSTT1 and null GSTM1, as observed by Singh et al 7 On the other hand, a Chinese study has shown a correlation between the double null genotype GSTT1 and GSTM1 with nasopharynx cancer among men.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…[38][39][40][41] In a multivariate logistic analysis, we have evidenced that the GSTT1/GSTM1*0 ([ ]/ [-]) combined genotype provides a greater susceptibility for the development of spinocellular carcinoma of head and neck, similar results to those found by other authors. 7,23,42,43 Various studies could not correlate the null GSTT1 genotype with the head and neck cancer, 26,27,43 which was a result found in our study. Similarly, there was no association between this type of neoplasia and the null combined genotypes null GSTT1 and null GSTM1, as observed by Singh et al 7 On the other hand, a Chinese study has shown a correlation between the double null genotype GSTT1 and GSTM1 with nasopharynx cancer among men.…”
Section: Discussioncontrasting
confidence: 68%
“…Studies relating these polymorphisms of deletion with the occurrence of head and neck carcinoma diverge between themselves: some demonstrate the association of these neoplasias with the null genotype of GSTM1, 7,21,[23][24][25] while others do not. [26][27][28][29][30] The same occurs with the null genotype of GSTT1, showing an association with the disease 7,23,25 or not. 26,27,[30][31][32] This way, the development of head and neck cancer is the result of the interaction between environmental factors and genetic heritage.…”
Section: Original Article Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerca de 40% dos tipos de câncer de cabeça e pescoço ocorrem na cavidade oral, 15% na faringe e 25% na laringe. O tipo histológico mais frequente, em 90% dos casos, é o carcinoma de células escamosas ou espinocelular, (BISELLI et al, 2006;CHISHOLM et al, 2007, HADDAD et al, 2008ALVARENGA et al, 2008).…”
Section: Zinco E Câncer De Cabeça E Pescoçounclassified